Analysis of plasma homocysteine levels in patients with chronic periodontitis before and after nonsurgical periodontal therapy using high-performance liquid chromatography - Gautami S Penmetsa; Rayapudi Uday Bhaskar; Anudeep Mopidevi (Wolters Kluwer Medknow Publications, 2020)
Introduction: Homocysteine (Hcy), an inflammatory biomarker, is a sulfur-containing amino acid. Elevated levels of plasma Hcy are evident in various inflammatory conditions and have been described as an independent risk factor for cardiovascular disease. The literature has also stated that a similar association could exist between the chronic periodontitis and plasma-Hcy levels, in otherwise systemically healthy individuals. However, studies on Hcy levels in periodontitis are scarce. Hence, this study aimed to assess the levels of plasma Hcy in patients with chronic periodontitis before and after nonsurgical periodontal therapy. Materials and Methods: This longitudinal, case-control clinical study included a total of 60 patients who were divided into two groups. Periodontal parameters including Plaque Index, Gingival Index, Sulcus Bleeding Index, probing depth, and clinical attachment level were recorded at baseline and 12 weeks after periodontal therapy. A high-performance liquid chromatography analysis was performed to measure the Hcy levels. The results were evaluated statistically for intergroup pair-wise comparisons by Mann-Whitney U-test and intragroup comparison by Wilcoxon-matched pairs test. Correlation between the plasma-Hcy levels with other clinical parameters in all groups was done by Spearman's rank correlation method. Results: The Hcy was detectable in all the samples. At baseline, the mean levels of plasma Hcy were found to be low in the control group, whereas in the test group, it is found to be higher. These plasma-Hcy levels and all periodontal parameters were reduced significantly after nonsurgical periodontal therapy. Conclusion: The results demonstrated that plasma-Hcy levels are reduced after nonsurgical periodontal therapy but not to the levels comparable with those found in healthy individuals. Therefore, nonsurgical periodontal therapy may be used as an adjunctive Hcy-lowering therapy, contributing toward primary prevention against cardiovascular diseases.